Antioxidant activity of the melanin pigment extracted from Aspergillus nidulans - Goncalves, RDR; Pombeiro-Sponchiado, SR (Pharmaceutical Soc Japan, 2005)
Melanins are pigments of high molecular weight formed by oxidative polymerization of phenolic or indolic compounds. A number of fungi, including Aspergillus nidulans, produce pigments related or identical to melanin, which are located on cell walls or exist as extracellular polymers. The aim of the present study was to assess the antioxidant activity of synthetic melanin and of the pigment extracted from the mycelium and culture medium after growth of the highly melanized strain (MEL1) from A. nidulans. The ability of the melanin pigment to scavenge the oxidants HOCl and H2O2 was evaluated by inhibition of the oxidation of 5-thio-2-nitrobenzoic acid (TNB) using several melanin concentrations. The results showed that the pigment of the MEL1 strain competes with TNB for H2O2 and HOCl, inhibiting TNB oxidation in a concentration-dependent manner. For the HOCl oxidant, this inhibition was comparable to that of synthetic melanin, whose IC50 values were quite close for both pigments. Thus, our results suggest that the melanin from A. nidulans is a potential HOCl scavenger and may be considered a promising material for the cosmetic industry for the formulation of creams that protect the skin against possible oxidative damage.
Keywords: fungi; melanin; pigment; antioxidant activity; Aspergillus nidulans